Flight Path Reconstruction and Parameter Estimation Using Output-Error Method - Benedito Carlos de Oliveira Maciel; Luiz Carlos Sandoval Góes; Elder Moreira Hemerly; Nei Salis Brasil Neto (Shock and Vibration)
This work describes the application of the output-error method using the Levenberg-Marquardt optimization algorithm to the Flight Path Reconstruction (FPR) problem, which constitutes an important preliminary step towards the aircraft parameter identification. This method is also applied to obtain the aerodynamic and control derivatives of a regional jet aircraft from flight test data with measurement noise and bias. Experimental results are reported, employing a real jet aircraft, with flight test data acquired by smart probes, inertial sensors (gyrometers and accelerometers) and Global Positioning Systems (GPS) receivers.